1987
DOI: 10.1111/j.1745-6584.1987.tb02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Universal Kriging to an Aquifer Study in New Jersey

Abstract: This article describes the use of kriging for optimizing data collection and utility in a regional ground‐water investigation of the Potomac‐Raritan‐Magothy aquifer system in central New Jersey. Kriging was used to (1) estimate the altitude of an aquifer surface, (2) estimate hydraulic conductivities from point data, and (3) estimate the associated kriged errors. The selection of locations for additional data collection, based on the kriged errors, was effective in terms of improving the aquifer surface data b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 5 publications
2
13
0
2
Order By: Relevance
“…Similar study has been reported by Pucci and Murashige (1987). They used kriging for optimising data collection and utility in a regional ground water investigation in central New Jersey and showed that kriging is a useful tool to elucidate those areas lacking enough data for developing a water table management network.…”
supporting
confidence: 64%
“…Similar study has been reported by Pucci and Murashige (1987). They used kriging for optimising data collection and utility in a regional ground water investigation in central New Jersey and showed that kriging is a useful tool to elucidate those areas lacking enough data for developing a water table management network.…”
supporting
confidence: 64%
“…Furthermore, based on the error map (standard deviation of estimations) they suggested a network for groundwater management. Similar study has been reported by Pucci and Murashige (1987). They used kriging for optimizing data collection and utility in a regional ground water investigation in central New Jersey and showed that kriging is a useful tool to elucidate those areas lacking enough data for developing a water table management network.…”
Section: Introductionsupporting
confidence: 66%
“…Since a periodic trend was seen in data set, a sine function was used to model the trend (Goovaerts, 1997). Kumar and Ahmed (2003), Pucci and Murashige (1987), Rouhani and Wackernagel (1990), Sophocleous et al (1982) and Tonkin and Larson (2001) also reported a trend in the data set of groundwater level and used the universal kriging to geostatistically analysis their data. More details on universal kriging can be found in Goovaerts (1997), Ma et al (1999) and Noshadi and Sepaskhah (2005).…”
Section: Temporal Analysismentioning
confidence: 96%
“…Kriging provides the best linear unbiased estimation for spatial interpolation [32,33]. We estimated regional shallow groundwater table depths by Kriging interpolation method.…”
Section: Methodsmentioning
confidence: 99%